KOMITMEN INDONESIA DALAM PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ORANG BERDASARKAN INSTRUMEN HUKUM INTERNASIONAL - Stogmuller, Katharina (Justitia et Pax, 2025)
This research focuses on human trafficking in Indonesia. The Indonesian government has ratified several international agreements such as the United Nations Convention Against Transnational Organized Crime (UNCTOC), Protocol to Prevent, Suppress and Punish Trafficking in Person, Especially Women and Children (Palermo Protocol), Protocol against the Smuggling of Migrants by Land, Sea, and Air, ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP). However, cases of human trafficking agreements involving Indonesian citizens still show significant numbers. This research uses a normative legal research method, focusing on international agreements adopted by the Indonesian government, including multilateral, regional,  bilateral agreements, and memorandum of understanding (MoU) that relate to the prevention and handling of human trafficking. This research finds out that although the Indonesian government has undertaken various efforts to prevent human trafficking the effectiveness of their implementation remains constrained.